PULAU GALANG SEBAGAI PENAMPUNGAN PENGUNGSI VIETNAM - Bunari Bunari Bunari (SEUNEUBOK LADA: Jurnal ilmu-ilmu Sejarah, Sosial, Budaya dan Kependidikan, 2017)
Galang Island known in the past Royal Malay (Kerajaan Melayu) as the hiding place of the Lanon (Pirates) also a topic of discussion of the international community when the United Nation High Commissioner For Refugees (UNHCR) placement of refugees "boat people" from Vietnam were stranded in several islands of the Riau archipelago Indonesia. The Vietnamese refugees came the first time on May 22, 1975 in marine waters West Bunguran Northern Natuna Island, Riau Islands which initially only 24 people in a short time reached a peak to 250,000 people. This research was conducted using the method of history that can be interpreted as a method of research and writing of history by using the method, a systematic procedure or technique in accordance with the principles and rules of the science of history. Then, be expected with this study obtain information on Indonesian nation in the International arena of caring helping refugees who vacillate in the sea to be rescued.